Performance of Grafted Bitter Gourd (Momordica charantia L.) at Different Pruning and Nitrogen Levels in Nawalparasi East, Nepal - Kandel, Renuka; Sah, Shrawan Kumar (Nepalese Horticulture, 2023)
Pruning and level of nitrogen influence the growth and yield of bitter gourd. A field experiment was conducted to assess the effect of different pruning and nitrogen levels on the growth and productivity of bitter gourd from March to July 2022 in Nawalparasi East, Nepal. The field experiment was laid out in a split-plot design with three replications. The treatment comprised three levels of pruning (No pruning, second generation (2G) pruning, and third generation (3G) pruning) in main plots and three different doses of nitrogen (100, 150, and 200 kg ha-1) in sub-plots. Observations on growth, floral, and yield parameters were recorded, analyzed, and presented. The research result revealed that 3G pruning with 200 kg ha-1 nitrogen level produced the highest fruit yield (16242.56 kg ha-1) at the fourth harvest. The yield trend showed higher fruit yield at higher nitrogen levels and 3G pruning at all dates of harvest. The increased fruit yield at higher nitrogen levels was because of more number of fruits per plant as well as longer fruit length and larger fruit diameter. The higher productivity in 3G pruning was mainly due to more fruit per plant at the fourth harvest. The results indicate a higher yield of bitter gourd at a higher level of nitrogen with 3G pruning.